Evaluation of the Efficacy of Different Pterygium Surgeries in Polish Caucasian Population - Marcin Palewski; Agnieszka Budnik; Łukasz Lisowski; Joanna Konopińska (Journal of Ophthalmology)
The aim of the study was to compare the efficacy of the two most commonly used surgical methods for pterygium removal in the Polish population, conjunctival autograft versus amniotic membrane transplantation, and to evaluate the postoperative recurrence rate. A retrospective analysis of the medical records was conducted, including 65 patients who underwent surgery for primary or recurrent pterygium at an ophthalmology clinic in Bialystok, Poland, between 2016 and 2020. Surgical success (no regrowth) was achieved in almost half of the amniotic membrane patients (44%) and in most of the conjunctival autograft patients (79%), with statistical significance. The odds of successful surgery were 79% lower for subjects with amniotic membranes than for those with conjunctival autografts (OR with 95% CI = 0.21 (0.05; 0.94); p=0.045). Our study confirms that the conjunctival autograft surgeries present more favorable success rates in Polish Caucasian population when compared to procedures involving amniotic membranes.